Mediation of Presence and Search of Meaning in Life between Spiritual Experience and Personal Growth - Embalsado, Justin Vianey M.; Apilado, Ralph Timothy G. (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2025)
The current study explored if Presence and Search for meaning in life mediate the relationship between Spiritual experience and Personal growth. 176 college students complete the meaning in life, spiritual experience, and personal growth surveys. JAMOVI GLM Mediation Model was used to understand the mediation of Presence and Search for Meaning. Findings indicate a full mediation of Presence of Meaning as a mediator between Spiritual experience and Personal growth. However, Search for Meaning fail to obtain a significant mediation. According to our findings, the Search for meaning does not predict Personal growth. Thus, people who perceive spiritual experience as a source of meaning could experience personal growth.